Comparative Studies on Plants as Bioindicator for Cu, Co, Ni, Pb, Zn, Cr, Fe, Mn, F and K2O in Lead-Zinc-Fluorite Mine Area of Chandidongri, Distt. Rajnandgaon (C.G.), India - Biswas, S.N. (Asian Journal of Chemistry, 2010)
Present studies were carried out on twelve tree species, viz., Azadirachta indica Adr. Juss., Buchanania lanzan Spreng, Cassia fistula L., Chloroxylon swietenia D.C., Ficus glomerata Roxb., Ficus retusa L., Holdenia cordifolia (Roxb.) Ridsd., Lagerstroemia parviflora Roxb., Madhuca indica J. Gmelin., Pterocarpus marsupium Roxb., Semecarpus anacardium L. and Stereospermum sauveolens D.C. in lead-zinc-fluorite mining area in Chandidongri district, Rajnandgaon. The concentration of the elements, viz., Cu, Co, Ni, Pb, Zn, Cr, Fe, Mn, F and K2O, were estimated from washed plant leaves and young twig samples which were collected from mineralized and nonmineralized areas. Chemical analysis of plants showed higher elemental concentrations for Cu, Co, Ni, Zn, Cr, Fe, Mn, F and K2O in comparison with the nonmineralized area plants and elemental composition of uncontaminated angiospermic plant tissues. The growth, distribution and toxic effects of plants of the mine area may be influenced by subsurface geology, reflecting the accumulation and toxic level of these elements.